Keterwakilan Perempuan PDIP di DPR RI Hasil Pemilu 2024: Analisis Normatif-Empiris Kebijakan Afirmasi Perempuan - Ardhana Ulfa Azis; Ofis Rikardo (Pagaruyuang Law Journal, 2026)
AbstractWomen’s representation in legislative bodies is a key indicator of an inclusive and gender-equitable democracy. Indonesia has implemented affirmative action policies in the form of a minimum 30% quota for women’s representation in political party leadership and legislative candidacy. However, the increase in the number of female candidates has not fully translated into a corresponding increase in the representation of elected women in parliament. This paper aims to analyze the implementation of the 30% affirmative action policy for women’s representation in the Legislative Elections within the Indonesian Democratic Party of Struggle (PDI-P) using a normative-empirical research methodology. Normatively, this study examines the constitutional basis and regulations for women’s affirmative action, while empirically, it analyzes the implementation of this policy in electoral practice. The research findings indicate that, normatively, this policy has a strong legal foundation, both in the constitution, national legislation, and international instruments ratified by Indonesia, such as CEDAW. However, the implementation of affirmative action policies in electoral political practice within the PDIP still faces various obstacles, including those influenced by internal party factors, particularly leadership patterns and political recruitment mechanisms that are centralized in nature. Affirmative action policies within the PDIP remain largely normative and have not been followed by more progressive concrete actions. Keywords: Women's Affirmative Action Policies, Legislative Elections, Political Representation  AbstrakKeterwakilan perempuan dalam lembaga legislatif merupakan salah satu indikator penting dalam demokrasi yang inklusif dan berkeadilan gender. Negara Indonesia telah menerapkan kebijakan afirmasi berupa kuota minimal 30% keterwakilan perempuan dalam kepengurusan partai politik dan pencalonan legislatif. Namun, peningkatan kuantitas calon perempuan belum sepenuhnya berbanding lurus dengan peningkatan keterwakilan perempuan terpilih di parlemen. Makalah ini bertujuan untuk menganalisis implementasi kebijakan afirmasi 30% keterwakilan perempuan dalam Pemilu Legislatif di Partai Demokrasi Indonesia Perjuangan melalui metodologi penelitian normatif-empiris. Secara normatif, penelitian ini mengkaji dasar konstitusional dan regulasi afirmasi perempuan, sedangkan secara empiris menelaah implementasi kebijakan tersebut dalam praktik pemilu. Hasil penelitian bahwa secara normatif, kebijakan ini telah memiliki dasar hukum yang kuat, baik dalam konstitusi, peraturan perundang-undangan nasional, maupun instrumen internasional yang telah diratifikasi Indonesia, seperti CEDAW. Namun implementasi kebijakan afirmasi dalam praktik politik elektoral kasus di PDIP masih menghadapi berbagai kendala antara lain dipengaruhi oleh faktor internal partai, terutama pola kepemimpinan dan mekanisme rekrutmen politik yang bersifat sentralistik. Kebijakan afirmasi di internal PDIP masih bersifat normatif dan belum diikuti tindakan khusus yang lebih progresif. Kata kunci: Kebijakan Afirmasi Perempuan, Pemilu Legislatif, Keterwakilan Politik